Effectiveness health education and infant therapeutic group therapy on baby aged 0-6 months to prevent stunting risk factors: mother depression - Wita Oktaviana (PAGEPress Publications, 2021)
Background: Stunting is a global and national problem that can be detected at the age of 2. Therefore, before this age, promotion efforts must be conducted to prevent stunting risk factors in the future. This study aims to determine the effect of health education and infant's Therapeutic Group Therapy on stunting's risk factor: maternal postpartum depression in Indonesia. Design and Methods: This study employed a quasi-experimental design with a pre-test and post-test with a control group. This study employed a purposive sampling technique, with 96 respondents divided into two groups. Intervention group 1 consisted of 48 people who received health education, and group 2 consisted of 48 people who received health education and infant's Therapeutic Group Therapy. The data were collected using the Depression Inventory-II (DI II) questionnaire with a bivariate analysis of the Wilcoxon test and frequency distribution. Results: The results show that health education and infant's Therapeutic Group Therapy significantly influence the risky factors in stunting: maternal depression. It can be concluded that there were significant changes in maternal postpartum depression in intervention group 1 and intervention group 2, but in intervention group 2 who got Health Promotion and Therapeutic Group Therapy (TKT) for Infants there was a bigger and more significant decrease. Conclusions: Nursing action, infants' Therapeutic Group Therapy, and health education are recommended to prevent risk factors for stunting: mother depression. The results of this study are expected to underlie the development of mental health promotion to prevent stunted against maternal depression and preventive programs. In addition, the research is expected to underly provision of curative and rehabilitative programs for stunted.